2021
DOI: 10.1016/j.isci.2021.103283
|View full text |Cite
|
Sign up to set email alerts
|

Increased gaze cueing of attention during COVID-19 lockdown

Abstract: Affiliation with others is a basic human need. The lockdown implemented for counteracting the COVID-19 pandemic has determined an unprecedented situation of social deprivation, forcing individuals to dramatically reduce face-toface interactions. This, in turn, has caused relevant consequences on psychological well-being. However, the impact of lockdown-related social isolation on basic cognitive processes is still largely unknown. Here, we focus on social attention and address gaze cueing, namely the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…For instance, affective priming (Ishikawa et al, 2021) and being primed with rejection-related thoughts (Wilkowski et al, 2009) have been shown to enhance gazecueing effects. Moreover, a recent study (Dalmaso et al, 2021) provided evidence that social deprivation results in a magnified responsiveness to the gaze direction of others. All these studies share a common definition of context, namely, the observer's background internal states while performing the task.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, affective priming (Ishikawa et al, 2021) and being primed with rejection-related thoughts (Wilkowski et al, 2009) have been shown to enhance gazecueing effects. Moreover, a recent study (Dalmaso et al, 2021) provided evidence that social deprivation results in a magnified responsiveness to the gaze direction of others. All these studies share a common definition of context, namely, the observer's background internal states while performing the task.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is here shown that spontaneous categorization processes are triggered, grouping individuals as a function of their mask-related behaviors. The implementation of preventive behaviors has become an integral part of people's daily lives, and much has already been done to highlight the possible effects on socio-cognitive processes 9,[52][53][54][55][56][57] . Although there is a widespread hope that we could soon overcome the Covid-19 pandemic, there is still uncertainty about the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results suggest that the pandemic did not have an impact on attentional mechanisms, relating either to “emotional” or “non-emotional” stimuli. Previous literature showed that the COVID-19 lockdown was associated with poorer cognitive performance ( 54 , 55 ) and increased attention toward social cues ( 56 ). Our findings seem to go against these results; this discrepancy likely reflects the specific components investigated and the measures used, since previous studies primarily focused on working memory (especially using n-back tasks) or gaze cueing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…When considering our experimental design, it is important to compare the EST to a task that assesses purely cognitive processes, not influenced by emotional or distressing features. Indeed, some studies have shown that COVID-19-related anxiety is associated with poorer cognitive performance ( 54 , 55 ), as well as increased attention toward social cues ( 56 ). One of the most relevant and frequently used approaches to studying visual cognitive processing is through visual search tasks ( 57 , 58 ).…”
Section: Introductionmentioning
confidence: 99%